African swine fever virus QP383R dampens type I interferon production by promoting cGAS palmitoylation - Hao, Siyuan; Zheng, Xiaojie; Zhu, Yingqi; Yao, Yao; Li, Sihan; Xu, Yangyang; Feng, Wen-hai (Frontiers in Immunology, 2023)
Cyclic GMP-AMP synthase (cGAS) recognizes viral DNA and synthesizes cyclic GMP-AMP (cGAMP), which activates stimulator of interferon genes (STING/MITA) and downstream mediators to elicit an innate immune response. African swine fever virus (ASFV) proteins can antagonize host immune responses to promote its infection. Here, we identified ASFV protein QP383R as an inhibitor of cGAS. Specifically, we found that overexpression of QP383R suppressed type I interferons (IFNs) activation stimulated by dsDNA and cGAS/STING, resulting in decreased transcription of IFNβ and downstream proinflammatory cytokines. In addition, we showed that QP383R interacted directly with cGAS and promoted cGAS palmitoylation. Moreover, we demonstrated that QP383R suppressed DNA binding and cGAS dimerization, thus inhibiting cGAS enzymatic functions and reducing cGAMP production. Finally, the truncation mutation analysis indicated that the 284-383aa of QP383R inhibited IFNβ production. Considering these results collectively, we conclude that QP383R can antagonize host innate immune response to ASFV by targeting the core component cGAS in cGAS-STING signaling pathways, an important viral strategy to evade this innate immune sensor.